Unleashing the Power of Digital Farming: Local Young Farmers’ Perspectives on Sustainable Value Creation - Norbertus Citra Irawan; Irham Irham; Jangkung Handoyo Mulyo; Any Suryantini (AGRARIS: Journal of Agribusiness and Rural Development Research, 2023)
A new challenge has emerged: how to implement innovations in agriculture? The expansion of digital technology has created new opportunities within the agricultural sector, particularly for young farmers, enabling the integration of information and communication technology into digital farming. Employing innovation diffusion theory, this study seeks to ascertain how young farmers perceive the integration of digital technology into various aspects of farming and how these views influence the formation of sustainable value creation. The study area was determined purposively, and this research utilized the case study method by interviewing 80 respondents. The data were analyzed using structural equations and partial least squares models. Using the innovation diffusion theory, the results unveiled that knowledge, persuasion, decision, implementation, and confirmation from young farmers significantly and positively affected the sustainable value creation.